Peramalan Harga Eceran Cabai Merah Menggunakan Fuzzy Time Series - Lilis Harianti Hasibuan; Syarto Musthofa; M Syahrul Ridho Nasution (UIN Imam Bonjol Padang, 2023)
Red chilies are a type of staple ingredient that is consumed by the wider community every day. Changes in the price of red chilies always occur from time to time. Therefore, it is important to carry out forecasting to consider decisions, both from buyers, traders and investors. The forecasting method that can be applied to this problem is the Fuzzy Time Series method with a classical approach. This method uses a fuzzy set as the basis for the forecasting process. The research results show that the forecast value of retail prices for red chilies follows the data pattern of actual red chili price movements. This is proven by the Mean Absolute Percentage Error (MAPE) forecasting accuracy value of .